Instagram's impact on dental consumers: analyzing toothpaste hashtags - Al-Khalifa, Khalifa S.; AlSheikh, Rasha; Alakloby, Basmah O.; Alharbi, Hind M.; Alghamdi, Razan F.; Ali, Saqib; Al Dehailan, Laila (Frontiers in Oral Health, 2025)
BackgroundToothbrushing is the basic step in maintaining oral hygiene and managing caries. The type of toothpaste used, combined with effective toothbrushing techniques, significantly influences oral health outcomes. Information shared on social media platforms can create awareness, generate interest, and influence perceptions regarding toothpaste brands and their benefits. This raised the necessity to comprehensively understand the influence of social media, particularly Instagram, on consumer decision-making processes and behavior related to toothpaste selection.Aimto explore toothpaste-related content on Instagram by addressing this gap and highlighting the characteristics of the top-performing toothpaste posts. Method: data were acquired for the “Top 12 posts” for each selected hashtag listed by the Instagram search algorithm. The contents of each post, including the number of likes, number of followers, content type, poster role, post content, post theme, post type, and account type were collected. Moreover, whether the poster was a dentist, patient, or dental interest group was identified. Data was then analyzed using SPSS with a statistical significance level set at p = .05.ResultsThe study analyzed a total of 1,054,985 posts revealing varying levels of engagement and content characteristics. Notably, the #Toothpaste hashtag garnered the highest number of posts, while #ToothpasteNatural had the lowest. Posts were predominantly promotional (61.1%) compared to educational (38.9%), with marketing being the primary theme. Educational content attracted significantly more engagement, with more likes/views and comments than promotional content. Additionally, the role of the poster influenced content type, with patients and dentists associated more with educational content, while dental interest groups and companies favored promotional material. However, there was no significant difference in the accuracy of claims between educational and promotional content.ConclusionInstagram shapes consumer behavior in toothpaste selection, with promotional content dominating despite higher engagement with educational posts. Limited fact-based content highlights the need for stricter regulations and increased contributions from dental professionals to improve oral health education.